PENGGUNAAN SOFTWARE ANALISIS STRUKTUR DALAM MATA PELAJARAN MEKANIKA TEKNIK UNTUK MENINGKATKAN PEMAHAMAN TENTANG ANALISIS STRUKTUR SISWA SMK JURUSAN TEKNIK BANGUNAN - Pradya Arhain Darlestio (CV. ADIBA AISHA AMIRA, 2025)
Vocational High School (VHS) majoring in Building Engineering plays a crucial role in enhancing students' understanding of structural concepts. The utilization of software in teaching at VHS not only aids students in comprehending theories but also provides them with real-world experiences, enabling them to apply these concepts in everyday life situations. Through integrated case studies and simulation projects within the curriculum, students deepen their understanding of both theory and practice, thus enhancing their overall comprehension. The impact of using structural analysis software in teaching engineering mechanics at VHS majoring in Building Engineering extends beyond the classroom, significantly influencing the quality of technical education as a whole. By preparing students for challenges in the workforce, the use of this software contributes significantly to producing graduates who are ready to compete and succeed in the construction industry. Therefore, the integration of technology in education at VHS Building Engineering not only enriches students' learning experiences but also opens doors to better career opportunities in the future